The impact of stationary ball-handling drills on fundamental offensive basketball skills in 13 and 14-year-old basketball players - Jakovljevic, S.; Pajic, Z.; Gardasevic, B.; Jankovic, N. (Facta Universitatis: Series Physical Education and Sport, 2015)
The aim of this study was to investigate the effect of no dribble stationary ball-handling drills on basic offensive skills in basketball. Participants were 121 young male basketball players aged 13-14 (M=13.59±0.54) who spent at least two years training basketball (M=3.30±0.74). Three no dribble stationary ball-handling drills were applied for independent variables: Double Leg-Single Leg (Dlsl30), Body Circles (Hwlb30) and Pretzel (Blur30). Three tests of offensive basketball skills, suggested by AAPRHED (1984), were applied for dependent variables: Speed spot shooting (Shooting), Passing test (Pass) and Control dribble test (Dribble). The impact of independent variables on the individual dependent variables was tested by using regression analysis - Stepwise method. Results showed that there was a significant impact of no dribble stationary ball-handling drills on basic offensive skills in basketball. Body circles drill had a significant impact on all three basketball skills, Pretzel drill had influence on shooting and passing, and Double Leg-Single Leg on passing and dribble. These results justify the use of no dribble stationary ball-handling drills in learning fundamental offensive basketball skills.